Use of nudges to improve food safety in the pork value chain in Uganda - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
A pilot based on evidence from ILRI-led assessments was conducted. It included nudges for meat handlers in Kampala to improve compliance with five areas of food safety. Based on results (available after A4NH ends), nudges may be included in training curriculum for 600 meat handlers in Uganda.